Exposure to Total Hydrocarbons During Cleanup of the Deepwater Horizon Oil Spill and Risk of Heart Attack Across 5 Years of Follow-up. Issue 5 (29th January 2019) - Strelitz, Jean; Sandler, Dale P; Keil, Alexander P; Richardson, David B; Heiss, Gerardo; Gammon, Marilie D; Kwok, Richard K; Stewart, Patricia A; Stenzel, Mark R; Engel, Lawrence S
Abstract: Exposure to total hydrocarbons (THC) and volatile organic compounds from air pollution is associated with risk of coronary heart disease. THC exposure from oil spills might be similarly associated, but no research has examined this. We assessed the relationship between THC exposure during the response and cleanup of the Deepwater Horizon oil spill (Gulf of Mexico) and heart attack risk among 24, 375 oil spill workers enrolled in the Gulf Long-Term Follow-up Study. There were 312 first heart attacks (self-reported physician-diagnosed myocardial infarction, or fatal coronary heart disease) ascertained during the study period (2010–2016). THC exposures were estimated using a job-exposure matrix incorporating self-reported activities and personal air measurements. We used Cox proportional hazards regression to estimate hazard ratios, with inverse-probability weights to account for confounding and censoring. Maximum THC levels of ≥0.30 parts per million (ppm) were associated with heart attack risk, with a 1.8-fold risk for exposure of ≥3.00 ppm versus <0.30 ppm (hazard ratio = 1.81, 95% confidence interval: 1.11, 2.95). The risk difference for highest versus lowest THC level was 10 excess cases per 1, 000 workers. This is the first study of the persistent health impacts of THC exposure during oil spill work, and results support increased protection against oil exposure during cleanup of future spills.